EFEKTIVITAS PROGRAM REHABILITASI BERSUMBER DAYA MASYARAKAT DENGAN METODE WHO TERHADAP PENGETAHUAN DAN KETERAMPILAN KADER PROVINSI SUMATERA UTARA TAHUN 2020 - Sinaga, Sudirman Pardingotan (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Prevalence disability in north sumatra provinve is 2.8 % - 20 % .The condition of environmental factor with disability and make people with a disability often ignored by the community. So that it difficult to people with a disability develop and access to health services . So They needs Community Based Rehabilitation (CBR) programme. CBR in indonesia has been operating for more than 25 years. CBR was acknowledged as an effective approach to solving problems associated with disability. CBR programmes are founded on basic ideas or concepts that vary significantly between countries and organizations. In 2010 the WHO has developed CBR matrix. Rehabilitation is the essential element in the matrix. As a health strategy, rehabilitation can improve functioning, quality of life and participation in society. PRM doctors contribute to the design and management of CBR strategies and to act as trainer for persons (professionals and non-professionals) who deliver rehabilitation interventions. Method on this research is quasi experimental. Research has been done in Lestari Indah village, Simalungun Regency, North Sumatra Province. There are 12 subject in this study divided into 2 groups. Group 1 training program with the organization and training combine with provision the manual book of CBR. Group 2 only given manual book of CBR. In both groups the has undergone a review by 3 experts in the field of CBR. The questionare was conducted before and after Intervention. CBR programme was done on 15-17 june 2020. The results of this study is there is 12 subject to participate in this research, divided into 2 groups. In the analysis of both groups, there are statistically significatly increase the components of the knowledge and skill component in the program after conducting CBR programme on group 1 but on group 2 there aren’t significantly.